Genius Hour Makes Great Teachers Redundant: What happens when Genius Hour really works? One teacher finds out firsthand that the plan to engage students in learning has unintended consequences. Issue 4 (April 2015) - Allen, Megan
In this satirical article, one teacher finds out that implementing Genius Hour in her classroom has unintended results. Genius Hour, modeled after Google's policy of allowing employees to spend 20% of their time working on a project of their own choosing, allows students to work on a project that follows their own passion.